The Effect of Work Competency and Commitment on Teacher Performance in State SMA 13 Medan - Nurul Dalimunte; Saimun Saimun (Jurnal Mantik, 2022)
In the world of teacher education, one of the supporting tools that play an important role in achieving national education goals is through the teaching and learning process. The purpose of this study was to determine the effect of competence on teacher performance, commitment at SMA Negeri 13 Medan, to determine the effect of competence and work commitment of teachers together on teacher performance at SMA Negeri 13 Medan. This researchthe sample is 61 teachers. Analysis of the hypothesis using SPSS 16.Research results: 1). The magnitude of the influence of competence on teacher performance as shown by the results of the study is 47.7meaning that competence has a good influence on teacher performance. 2).The magnitude of the effect of work commitment on teacher performance as shown by the results of the study is 36.6% This means that in improving teacher performance, one of the variables that influence it is teacher work commitment. 3).The magnitude of the effect of competence and work commitment on teacher performance is shown by the results of the study of 83.3%.